Takaran Optimal Pupuk NPKS, Dolomit, dan Pupuk Kandang pada Hasil Kedelai di Lahan Pasang Surut - Taufiq, Abdullah; Wijanarko, Andy; Suyamto, Suyamto (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Tidal swamp land has a good potential for soybean production. The main obstacle found on this land are low soil fertility, acidic reaction and high alluminium. The study was aimed to determine the optimal rate of fertilizer, and the effect of dolomite and manure on soybean yield on tidal swamp land. The experiment was conducted on a tidal land type C in Rantau Rasau, East Tanjung Jabung, Jambi Province, in 2009. The experiment used a completely randomized block design with three replications. The treatment consisted of a combination of fertilizers N, P, K, S, dolomite, and manure. The results showed that a high soybean yield on the tidal land type C can be obtained by applying NPKS fertilizers, dolomite, and manure with a rate of 30-30-30-20 (N-P2O5-K2O-SO4) kg/ha or equivalent to 200 kg compound fertilizer/ha. The NPKS fertilizer can be reduced by 50%, if it is combined with 750 kg/ha of dolomite and 1000 kg/ha organic manure. Addition of dolomite and manure increased the efficiency of the NPKS fertilizer.